Tissue factor expression in neutrophil extracellular traps and neutrophil derived microparticles in antineutrophil cytoplasmic antibody associated vasculitis may promote thromboinflammation and the thrombophilic state associated with the disease. Issue 10 (19th July 2013) - Kambas, Konstantinos; Chrysanthopoulou, Akrivi; Vassilopoulos, Dimitrios; Apostolidou, Eirini; Skendros, Panagiotis; Girod, Andreas; Arelaki, Stella; Froudarakis, Marios; Nakopoulou, Lydia; Giatromanolaki, Alexandra; Sidiropoulos, Prodromos; Koffa, Maria; et al.
Abstract : Objectives: Antineutrophil cytoplasmic antibody (ANCA) associated vasculitis (AAV) is characterised by neutrophil activation. An elevated prevalence of venous thromboembolic events has been reported in AAV. Because of the critical role of neutrophils in inflammation associated thrombosis, we asked whether neutrophil tissue factor (TF) may be implicated in the thrombotic diathesis in AAV. Methods: Neutrophils from four patients and sera from 17 patients with ANCA associated vasculitis with active disease and remission were studied. TF expression was assessed by immunoblotting and confocal microscopy. Circulating DNA levels were evaluated. TF expressing microparticles (MPs) were measured by flow cytometry and thrombin–antithrombin complex levels by ELISA. Results: Peripheral blood neutrophils from four patients with active disease expressed elevated TF levels and released TF expressing neutrophil extracellular traps (NETs) and MPs. TF positive NETs were released by neutrophils isolated from the bronchoalveolar lavage and were detected in nasal and renal biopsy specimens. Elevated levels of circulating DNA and TF expressing neutrophil derived MPs were further observed in sera from patients with active disease. Induction of remission attenuated the aforementioned effects. Control neutrophils treated with sera from patients with active disease released TF bearing NETs and MPs which were abolished after IgG depletion. Treatment of control neutrophils with isolated IgG from sera from patients with active disease also resulted in the release of TF bearing NETs. TF implication in MP dependent thrombin generation was demonstrated by antibody neutralisation studies. Conclusions: Expression of TF in NETs and neutrophil derived MPs proposes a novel mechanism for the induction of thrombosis and inflammation in active AAV.